Improving Teachers’ Knowledge and Awareness on Gender-Responsive Teaching Through a School Learning Action Cell (SLAC) Session - Asia-Phil T Binongo (Journal of Education and Learning Research, 2026)
This study investigated the effectiveness of a School Learning Action Cell (SLAC) session in enhancing the knowledge and awareness of secondary teachers regarding gender-responsive teaching. Employing a quantitative one-group pretest–posttest design, thirty teachers participated in a SLAC session focused on integrating gender principles into instructional content, teaching strategies, and classroom management. A researcher-made questionnaire composed of Likert-scale items and situational questions was administered before and after the intervention. Descriptive results revealed a generally positive baseline understanding (M = 3.99, SD = 0.68), while posttest scores showed a significant increase in teachers’ knowledge and awareness (Pretest M = 8.90, SD = 2.50; Posttest M = 9.77, SD = 1.72). The paired-sample t-test indicated a statistically significant improvement, t(29) = –3.21, p = .003, with decreased score variability suggesting more consistent competence among participants. Findings confirm that a well-designed SLAC session can effectively strengthen teachers’ gender-responsive knowledge within a short timeframe. However, results also highlight lingering gaps in teachers’ confidence when handling complex gender-related scenarios, underscoring the need for follow-up, scenario-based capacity-building activities. Overall, the study provides empirical evidence that school-based, collaborative professional development can meaningfully support DepEd’s GAD agenda and contribute to more inclusive, equitable classroom practices.